FRICTIONAL PHENOMENA IN COAL MINES: REASONS, CONSEQUENCES AND INFLUENCE ON GAS DYNAMIC AND THERMAL PHENOMENA - BARANOV, Volodimir; ANTIPOVICH, Yana; STEFANKO, Serhii (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Coal mines are objects of increased danger, since dynamic, gas-dynamic and thermal phenomena occur in them. These phenomena lead to violations of the operating regime, the failure of mining equipment, the death of miners, an increase in the cost of coal mining and other consequences. The purpose of the article is to present the results of studies of the conditions for the formation of thermal effects in coal mines and the reasons for their occurrence, which has both scientific and applied relevance. The conducted studies made it clear that sparking can occur under the influence of both man-made and natural factors. Friction phenomena leading to thermodynamic effects have been recorded in many mines and countries of the world. The main part of explosions and fires of methane occurs during frictional sparking of rocks containing sulfides. The latter produce sparks of a sufficiently high temperature, which can lead to the ignition of combustible gases, as well as the release of hydrogen sulfide, which has a low ignition temperature. In world practice, cases of ignition of combustible materials during the landing of the roof in the absence of coal have been described. British researchers concluded that the methane-air mixture can be ignited by a spark generated by the friction of sandstone against sandstone or mudstone against sandstone. According to the literature data, the ignition of combustible materials and coals can occur as a result of: emissions and explosions, rock collapse during landing, when a spark discharge occurs in quartz during a tribo- or piezoelectric effect; the presence of sulfides in coals or rocks, pyroelectric effect; electrification of coals. At the micro level, in quartz grains of sandstones, the formation of static charges by dislocations, which are decorated with dust, has been established. A particularly strong effect can occur if, in addition to methane, carbon monoxide, hydrogen, hydrogen sulfide, and acetylene are present in the air. An increase in sparking during frictional friction of quartz in the presence of coal dust has been established. The presence of gas inclusions in sandstone minerals during shear deformations leads to the appearance of additional concentrations of hydrocarbons. As a result of contact of such a mixture with a heated area, a short-term small flash occurs, which is a spark.
Keywords: sparking; coals; sandstones; fire; static charge; rock disturbances